2017
DOI: 10.1111/jcmm.13070
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin promotes human jaw bone marrow mesenchymal stem cell chemotaxis via CXCL1 and CXCL8

Abstract: Adiponectin (APN) is known to promote the osteogenic differentiation of human jaw bone marrow mesenchymal stem cells (h‐JBMMSCs). However, the underlying mechanism has not been fully elucidated. Previously, we showed that APN could promote h‐JBMMSC osteogenesis via APPL1‐p38 by up‐regulating osteogenesis‐related genes. Here, we aimed to determine whether APN could promote h‐JBMMSC chemotaxis through CXCL1/CXCL8. The CCK‐8, wound healing and transwell assays were used to evaluate the proliferation, migration a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
2
10
0
Order By: Relevance
“…Previous studies have demonstrated that APN could attenuate lipid deposition and apoptosis through activating p38 MAPK pathway ( 37 , 38 ). In the present study, it was demonstrated that APN alone could induce p38 phosphorylation, which is in accordance with previous studies ( 39 , 40 ). Furthermore, Ang II promoted p38 phosphorylation.…”
Section: Discussionsupporting
confidence: 94%
“…Previous studies have demonstrated that APN could attenuate lipid deposition and apoptosis through activating p38 MAPK pathway ( 37 , 38 ). In the present study, it was demonstrated that APN alone could induce p38 phosphorylation, which is in accordance with previous studies ( 39 , 40 ). Furthermore, Ang II promoted p38 phosphorylation.…”
Section: Discussionsupporting
confidence: 94%
“…As determined by qRT‐PCR analysis, the expression of these genes was consistent with the dataset (Figure B and C). Previous studies have reported several of the above‐mentioned genes (CIDEC, MAOA, SAA1, SVEP1, FBLN2, ADARB1, ZBTB16, ANGPT1, FBLN1, FZD4, OMD, ABI3BP, RGS4, CXCL8) are closely related to bone homeostasis and the process of osteogenic differentiation, and these studies further supported the reliability of the dataset. To identify the BMSCs osteogenic differentiation‐related genes, we chose 10 of the other upregulated genes, namely EFHD1, FKBP5, APOD, ACTC1, SORT1, COMP, CLEC3B, CRYAB, WASF3, LMOD1, and downregulated their expression by specific siRNA in BMSCs (Figure D‐M).…”
Section: Resultssupporting
confidence: 72%
“…The chemokine GROα (CXCL1), a mediator of MSC chemotaxis [ 64 ], apparently contributes to the formation of a network of inflammatory cytokines/chemokines and one of the hematopoietic stem cell (HSCs) growth factors (SCGF-b) ( Figure 2 ). CXCL1, on the other hand, can induce osteoclastogenic activity [ 65 ].…”
Section: Resultsmentioning
confidence: 99%